2002
DOI: 10.1007/s00134-002-1473-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomized prospective trial of immediate vs. next-day feeding after percutaneous endoscopic gastrostomy in intensive care patients

Abstract: In acutely ill intensive and intermediate care patients immediate enteral feeding via a percutaneous endoscopic gastrostomy tube is as safe as next-day feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…In adults, early (3-6 hours) feeding is as safe as nextday feeding, is well tolerated, and decreases length of hospital stay (83)(84)(85)(86). Early refeeding starting after 6 hours and resumption of full feeding within 24 hours is also safe in children (87).…”
Section: Percutaneous Endoscopic Gastrostomy Placement: Preoperative mentioning
confidence: 94%
“…In adults, early (3-6 hours) feeding is as safe as nextday feeding, is well tolerated, and decreases length of hospital stay (83)(84)(85)(86). Early refeeding starting after 6 hours and resumption of full feeding within 24 hours is also safe in children (87).…”
Section: Percutaneous Endoscopic Gastrostomy Placement: Preoperative mentioning
confidence: 94%
“…The recommendation to delay feeding initiation until 12-24 h after PEG or transabdominal gastrostomy placement was based on a presumption that the GI system would return to normal function during this period of time, allowing a better seal of the enteral opening [46,67] . More recently, however, several prospective randomized studies have clearly demonstrated that, at least in the case of PEG placement, much earlier initiation of feeding after as little as 1-3 h is equally safe [68][69][70][71] . This was confirmed in a meta-analysis by Bechtold et al [72] .…”
Section: Initiation Of Feedingmentioning
confidence: 97%
“…In general, enteral feeding begins 12-24 hours postprocedure [4], given the clinical concern for leakage of gastric contents into the peritoneal cavity or aspiration after PEG placement. However, recent data support the safety of early gastric feeding without the need of intravenous fluids or caloric support [4,9,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%